Health-related quality of life with adjuvant ipilimumab versus placebo after complete resection of high-risk stage III melanoma (EORTC 18071): secondary outcomes of a multinational, randomised, double-blind, phase 3 trial. Issue 3 (March 2017) - Coens, Corneel; Suciu, Stefan; Chiarion-Sileni, Vanna; Grob, Jean-Jacques; Dummer, Reinhard; Wolchok, Jedd D; Schmidt, Henrik; Hamid, Omid; Robert, Caroline; Ascierto, Paolo A; Richards, Jon M; Lebbé, Celeste; et al.
Summary: Background: The EORTC 18071 phase 3 trial compared adjuvant ipilimumab with placebo in patients with stage III melanoma. The primary endpoint, recurrence-free survival, was significantly longer in the ipilimumab group than in the placebo group. Investigator-reported toxic effects of ipilimumab consisted mainly of skin, gastrointestinal, endocrine, and hepatic immune-related adverse events. Adjuvant treatment with ipilimumab in this setting was approved in October, 2014, by the US Food and Drug Administration based on the results of the primary outcome of this trial. Here, we report the results of the secondary endpoint, health-related quality of life (HRQoL), of this trial. Methods: EORTC 18071 was a multinational, double-blind, randomised, phase 3 trial in patients with stage III cutaneous melanoma (excluding lymph node metastasis ≤1 mm or in-transit metastasis) in 19 countries worldwide. Participants were randomly assigned (1:1) centrally by an interactive voice response system, to receive either ipilimumab 10 mg/kg or placebo every 3 weeks for four doses, then every 3 months for up to 3 years. Using a minimisation technique, randomisation was stratified by disease stage and geographical region. HRQoL was assessed with the EORTC QLQ-C30 quality-of-life instrument at baseline, weeks 4, 7, 10, and 24, and every 12 weeks thereafter up to 2 years, irrespective of disease progression. Results were summarised by timepoint and in a longitudinal manner in the intention-to-treat population. Two summary scores were calculated for each HRQoL scale: the average score reported during induction (ipilimumab or placebo at a dose of 10 mg/kg, administered as one single dose at the start of days 1, 22, 43, and 64—ie, four doses in 3 weeks), and the average score reported after induction. A predefined threshold of a 10 point difference between arms was considered clinically relevant. The primary HRQoL endpoint was the global health scale, with the predefined hypothesis of no clinically relevant differences after induction between groups. This trial is registered with EudraCT, number 2007-001974-10, and ClinicalTrials.gov, number NCT00636168 . Findings: Between July 10, 2008, and Aug 1, 2011, 951 patients were randomly assigned to treatment: 475 in the ipilimumab group and 476 in the placebo group. Compliance with completing the HRQoL questionnaire was 893 (94%) of 951 patients at baseline, 693 (75%) of 924 at week 24, and 354 (51%) of 697 at week 108. Patient mean global health scores during (77·32 [SD 17·36] vs 72·96 [17·82]; p=0·00011) and after induction (76·48 [17·52] vs 72·32 [18·60]; p=0·00067) were statistically significantly different between groups but were not clinically relevant. Mean global health scores differed most between the groups at week 7 (77 [SD 19] in the placebo group vs 72 [22] in the ipilimumab group) and week 10 (77 [20] vs 70 [23]). Mean HRQoL scores differed by more than 10 points at week 10 between treatment groups for diarrhoea (7·67 [SD 17·05] for placebo vs 18·17 [28·35] for ipilimumab) and insomnia (15·17 [22·53] vs 25·60 [29·19]). Interpretation: Despite increased toxicity, which led to treatment discontinuation for most patients during the induction phase of ipilimumab administration, overall HRQoL, as measured by the EORTC QLQ-C30, was similar between groups, as no clinically relevant differences (10 points or more) in global health status scores were observed during or after induction. Clinically relevant deterioration for some symptoms was observed at week 10, but after induction, no clinically relevant differences remained. Together with the primary analysis, results from this trial show that treatment with ipilimumab results in longer recurrence-free survival compared with that for treatment with placebo, with little impairment in HRQoL despite grade 3–4 investigator-reported adverse events. Funding: Bristol-Myers Squibb.